2006
DOI: 10.1007/s00417-006-0274-x
|View full text |Cite
|
Sign up to set email alerts
|

The antibody response in experimental ocular toxoplasmosis

Abstract: Our findings relating to the rabbit model of OT reveal three features of clinical relevance: a diagnostic window precedes the establishment of a humoral immune response; specific antibodies persist long after the cessation of disease activity; and in primary OT, the antibody ratio C may also increase in the uninfected partner eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Patients with acquired disease, in contrast, manifest more uniformly a marked inflammatory response and usually harbour high levels of specific antibodies 31. In a rabbit model of acquired ocular toxoplasmosis, we have shown that high levels of local antibodies may persist over several months 32. Based on these observations, one might argue that patients with a stronger immune response and persisting high local antibody concentrations, that is otherwise healthy young patients with acquired disease, may achieve a better protection against reactivation, but this has as yet to be shown.…”
Section: Discussionmentioning
confidence: 92%
“…Patients with acquired disease, in contrast, manifest more uniformly a marked inflammatory response and usually harbour high levels of specific antibodies 31. In a rabbit model of acquired ocular toxoplasmosis, we have shown that high levels of local antibodies may persist over several months 32. Based on these observations, one might argue that patients with a stronger immune response and persisting high local antibody concentrations, that is otherwise healthy young patients with acquired disease, may achieve a better protection against reactivation, but this has as yet to be shown.…”
Section: Discussionmentioning
confidence: 92%
“…In a significant proportion of patients (21%), a clinically relevant time lapse has to be expected between the onset of clinical symptoms and the activation of local antibody production, and this circumstance has been confirmed in a lapine model of ocular toxoplasmosis [53). In infection-naïve animals, the time lapse between inoculation with tachyzoites of Toxoplasma gondii and the local activation of specific antibody production may be up to 2 weeks.…”
Section: Time Lapse Between the Onset Of Symptoms And The Induction Omentioning
confidence: 99%
“…The time lapse between the onset of the symptom and the induction of a local immune response is not clearly established and is always disputed. In a rabbit model of OT, the local activation of specific antibody production was found 2 weeks after inoculation of tachyzoite in naive animals and about 3 weeks in a rabbit model of reactivation 42. However, intraocular production of antibodies has been detected frequently in the first two weeks after the onset of symptoms in many patients.…”
Section: Discussionmentioning
confidence: 98%